Economic Growth in Prewar China - Rawski, Thomas G. (University of California Press, 1989)
This book's analysis of economic growth in China from the late nineteenth century to the Pacific War challenges the common notion that the prewar decades were a time of stagnation or decline. Focusing on the modern sector--cotton textile factories, sail and steamship transport, and Western-style commercial banking--Rawski demonstrates that, in spite of extreme economic and political uncertainty, the period saw significant economic growth. He portrays the transformation of China's economy as a long-term process spanning both sides of the 1949 political divide--economic progress did not await the arrival of socialism. China's recent turn toward the capitalist road lends added significance to this study, which illustrates the dynamic potential of the market system in a Chinese cultural setting.
Keywords: Chinese Business History; History / Asia / China; History / Asia / General